CGIAR One Health Initiative tackles food safety, zoonoses and antimicrobial resistance in Vietnam - Vietnam One Health Partnership for Zoonoses; Vietnam National Institute of Veterinary Research; International Livestock Research Institute (International Livestock Research Institute, 2025)
The CGIAR One Health Initiative (2022-2024), which is co-led by the National Institute of Veterinary Research (NIVR) under the Ministry of Agriculture and Rural Development, and the International Livestock Research Institute (ILRI), is addressing challenges related to human, animal, and environmental health. The initiative works in six provinces (Lao Cai, Hanoi, Thai Nguyen, Thua Thien Hue, Dong Nai, and Can Tho), focusing on controlling zoonotic diseases, ensuring food safety, and reducing antibiotic resistance. Key outcomes include surveillance of zoonotic diseases, improving hygiene in traditional markets and slaughterhouses, and raising awareness of proper antibiotic use.